The Death of Selective Waiver: How New Federal Rule of Evidence 502 Ends the Nationalization Debate - Emery, Patrick M. (Journal of Law and Commerce, 2009)
New Federal Rule of Evidence 502 (“FRE 502”) will end the threedecade push to nationalize a corporate litigation protection known as the “selective waiver doctrine.” First adopted by the Eighth Circuit in 1978, the selective waiver doctrine holds that, when a corporation discloses privileged materials to a government agency during an investigation, the corporation retains its privileges against third-party litigants—i.e., the corporation may selectively waive its attorney-client privilege (and in other circuits its attorney work product protection). This flies in the face of traditional waiver rules, under which a waiver of privilege to one’s adversary generally is a waiver to all adversaries on that subject matter. Based on years of frustration with discovery costs, fear of corporate fraud, and heavy burdens placed on administrative agencies, many legal scholars praised selective waiver as a cure for those ills. Recently, when the Advisory Committee on Evidence Rules met to discuss additions to the FRE, many called for the inclusion of a selective waiver provision. After much debate, the Advisory Committee determined that the selective waiver proposal for FRE 502 was too controversial. In its enacted form, FRE 502 does not contain a selective waiver provision.